Knowledge and application of bioethical principles among healthcare staff in the emergency department of Portoviejo General Hospital - Macías, Mauro H.; Moreira, María V.; Marín, Alfredo L. (Revista Gregoriana de Ciencias de la Salud, 2024)
The present study determined the level of knowledge and application of bioethical principles in health personnel in the emergency area of the Portoviejo General Hospital. A quantitative, observational, descriptive, cross-sectional, and correlational design was used, with a sample of 67 professionals selected through simple probabilistic sampling. A questionnaire about the level of knowledge of bioethical principles and a checklist to evaluate their application in clinical practice were used to collect the data. The data were processed through the Shapiro-Wilk test to assess their normality, and analysis of variance was performed. Additionally, the odds ratio determined the association between the level of knowledge and the application of bioethical principles. The results showed an equitable distribution by sex, a predominance of professionals between 35 and 44 years old, and a majority residing in Portoviejo. 30% of the staff showed limited knowledge of bioethical principles, and 20.90% did not apply them consistently, revealing a gap between theoretical knowledge and its practical application. Age had a significant effect (p ≤ 0.05) on knowledge and application of ethical principles, while sex did not show a relevant influence. These results show the need to improve bioethics training among health personnel in the emergency area and suggest the implementation of interventions aimed at closing the gap between knowledge and practice of these principles.